Pelatihan Penyusunan Capital Budgeting pada Pelaku Usaha Kecil Menengah di Kabupaten Banyumas - Purwidianti, Wida; Watemin, Watemin; Rahayu, Tri Septin Muji (Universitas Nusantara PGRI Kediri, 2024)
Micro, small and medium enterprises (MSMEs) are considered the engine that drives a country's economy. The research results showed that as many as 45% of MSMEs failed to continue their business. This community service partner is the Banyumas Regency Micro, Small and Medium Enterprises Association (ASPIKMAS) which has a membership of more than 5000 MSMEs. There are three problems faced by MSMEs, namely organizational management, fixed asset investment decisions and preparing capital budgeting. The solution offered to service partners is to carry out lectures and training activities on managing MSMEs, fixed asset investment and preparing capital budgeting. The results of this community service show an increase in partners' knowledge regarding management knowledge, fixed asset investment and capital budgeting methods. The results of community service also show an increase in partners' skills in preparing capital budgeting. The results of the partner satisfaction survey regarding the implementation of community service showed a very good assessment.